Bilateral central anterior stromal opacity of the cornea: dystrophy or degeneration? - TOKER, AYŞE EBRU (WICHTIG EDITORE, 2003)
PURPOSE. To describe a bilateral, central, oval corneal opacity not resembling any known corneal degeneration or dystrophy. METHODS. Ophthalmic examination, corneal topography, and pachymetry. RESULTS. A 30-year-old woman presented complaining of blurred vision. Biomicroscopic examination revealed bilateral, centrally located, oval, diffuse opacification of the anterior corneal stroma. Corneal topography showed slightly paracentral corneal flattening and irregular astigmatism in both eyes. Pachymetry indicated thinning of the central cornea in the left eye. No evidence of systemic disease was found. Family members had no corneal abnormalities. CONCLUSIONS. This unusual keratopathy closely resembles climatic proteoglycan stromal keratopathy. However, it is not clear whether the condition should be described as a dystrophy or degeneration.
Keywords: anterior stromal opacity; climatic proteoglycan dystrophy; corneal thinning; corneal flattening